Rút gọn biểu thức
A. x(x - 1) + 6(x - 3)(x + 3)
B. (2 - 3x)(2 + 3x) - (x + 5)(x - 5)
C. (3x + 1 )(x +5) - (x - 1)(x + 1)
D. (2 - 3x)(2x + 3) + 6(x - 1)^2
E. x(5 - x) - (2x + 2)(3x + 2) - (x - 2)(x + 2)
F. (2 - x)(2 + x) - 2x(x - 7) + x(x + 1)
. Giúp mình với mình đang cần gấp
A)\(x\left(x-1\right)+6\left(x-3\right)\left(x+3\right)\)
\(=x^2-x+6\left(x^2-9\right)\)
\(=x^2-x+6x^2-54\)
\(=7x^2-x-54\)
F.\(\left(2-x\right)\left(2+x\right)-2x\left(x-7\right)+x\left(x+1\right)\)
\(=4-x^2-2x^2+14x+x^2+x\)
\(=-2x^2+15x+4\)